2021
DOI: 10.1080/13416979.2021.1876587
|View full text |Cite
|
Sign up to set email alerts
|

The endangered epiphytic orchid Dendrobium okinawense has a highly specific mycorrhizal association with a single Tulasnellaceae fungus

Abstract: Epiphytic orchids, which account for 68% of vascular epiphytes, contribute substantially to plant species diversity in forest canopies. Many orchid species are naturally rare and have limited geographical distributions. All orchids rely on mycorrhizal fungi for nutrient acquisition during seed germination and seedling establishment, and many species retain these associations throughout their lifecycle. Due to their reliance on mycorrhizal fungi, epiphytic orchid species with highly specific mycorrhizal associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…Although D. officinale is associated with a wide range of basidiomycetous mycorrhizal partners, its main fungal partners may be widely shared among D. officinale populations. In Dendrobium okinawense, 11 mature plants from four sites were predominantly associated with a single Tulasnellaceae OTU (Rammitsu et al, 2021). Such high specificity is also found in Dendrobium fimbriatum, which was associated with only two OTUs in 15 root samples from two sites (Xing et al, 2013).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Although D. officinale is associated with a wide range of basidiomycetous mycorrhizal partners, its main fungal partners may be widely shared among D. officinale populations. In Dendrobium okinawense, 11 mature plants from four sites were predominantly associated with a single Tulasnellaceae OTU (Rammitsu et al, 2021). Such high specificity is also found in Dendrobium fimbriatum, which was associated with only two OTUs in 15 root samples from two sites (Xing et al, 2013).…”
Section: Discussionmentioning
confidence: 74%
“…The fungal isolates obtained in this study were deposited in the Biological Resource Center of the National Institute of Technology and Evaluation (NBRC) (Table 2). 10.3389/fevo.2022.994641 Molecular identification of mycorrhizal fungi DNA was extracted from root samples as described previously (Rammitsu et al, 2021). Samples were crushed with forceps to disperse hyphal coils into TE buffer.…”
Section: Fungal Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…The next study deals with an endangered epiphytic orchid, Dendrobium okinawense. Rammitsu et al (2021) investigated the symbiotic fungi of D. okinawense and found that this orchid has highly specific symbiotic fungi. The degree of symbiotic specialists is likely to relate closely to the forest health, suggesting that it is important to protect oldgrowth forests in Yambaru from anthropogenic disturbances for the conservation of this species.…”
Section: Quick Preview Of Special Issue Contentmentioning
confidence: 99%